2006
DOI: 10.1080/02652030600944395
|View full text |Cite
|
Sign up to set email alerts
|

Usage of saccharin in food products and its intake by the population of Lucknow, India

Abstract: A survey of the usage patterns of the artificial sweetener, saccharin, in edible products and a study of its intake pattern in different population groups has been carried out. Of the different edible commodities, ice candy (87 samples) and crushed ice (14 samples), commonly consumed by children, and pan masala (16 samples) and pan flavourings (10 samples), consumed by the habitual population, were collected from different areas of Lucknow, India. Saccharin was extracted from the samples according to an AOAC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…One study reported that tadpoles and 55 zebrafish exposed to 0.2% effluents from STPs showed a 40% 56 reduction in growth [9]. Another study showed that egg 57 production was decreased in Japanese medaka (Oryzias latipes) 58 following exposure to 0.5 mg/L of propranolol [24]. 59 This is a pilot study to elucidate the occurrence and removal of 60 43 widely used PPCPs (two antimicrobials, four antibiotics, an 61 antimycotic, four analgesics, an antihistamine, an antiplatelet, a 62 UV-filter, a stimulant, two antischizophrenics, six sedative- 63 hypnotics-anxiolytics, four antidepressants, four antihyperten- 64 sives, eight illicit drugs, and four artificial sweeteners) and 13 New York, and stored in a freezer at À20 C until extraction.…”
Section: Introductionmentioning
confidence: 95%
“…One study reported that tadpoles and 55 zebrafish exposed to 0.2% effluents from STPs showed a 40% 56 reduction in growth [9]. Another study showed that egg 57 production was decreased in Japanese medaka (Oryzias latipes) 58 following exposure to 0.5 mg/L of propranolol [24]. 59 This is a pilot study to elucidate the occurrence and removal of 60 43 widely used PPCPs (two antimicrobials, four antibiotics, an 61 antimycotic, four analgesics, an antihistamine, an antiplatelet, a 62 UV-filter, a stimulant, two antischizophrenics, six sedative- 63 hypnotics-anxiolytics, four antidepressants, four antihyperten- 64 sives, eight illicit drugs, and four artificial sweeteners) and 13 New York, and stored in a freezer at À20 C until extraction.…”
Section: Introductionmentioning
confidence: 95%
“…This is because certain food additives have often limited usage in food products and an accountability of this provides with information regarding extreme intake by high consumers. (57) So in studies on intake of artificial sweeteners, it makes sense to focus on population groups who are likely to consume more of artificial sweeteners, such as diabetics or those trying to lose/maintain weight. (55) …”
Section: Artificial Sweetenersmentioning
confidence: 99%
“…All the studies showed that the intake was found to be below the ADI, except a study that showed that intake of saccharin exceeded the ADI when sweetened crushed ice and ice candy was consumed by children and when sweetened betel leaf was consumed by adults. (57) In assessing exposure to food additives, a distinction needs to be drawn between average consumers and consumers who have above-average intake of individual foods. This is because certain food additives have often limited usage in food products and an accountability of this provides with information regarding extreme intake by high consumers.…”
Section: Artificial Sweetenersmentioning
confidence: 99%
“…It is also used in cosmetics, pharmaceutical products and nutritive and non neutritive sweeteners. [17][18][19][20] Recently, sodium saccharin as a basic green and easy available compound was used as catalyst in some organic syntheses. 21,22 We now report a new efficient and simple synthetic method, taking place via addition and subsequently cyclization of 2,5-dihydroxy-1,4-benzoquinone, arylaldehydes and malononitrile in the presence of a catalytic amount of sodium saccharine under microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%